Greater Nutrient Intake Is Associated With Lower Mortality in Western and Eastern Critically Ill Patients With Low BMI: A Multicenter, Multinational Observational Study. Issue 1 (30th June 2018) - Compher, Charlene; Chittams, Jesse; Sammarco, Therese; Higashibeppu, Naoki; Higashiguchi, Takashi; Heyland, Daren K.
Abstract: Background : Little is known about the impact of feeding adequacy by NUTrition Risk in the Critically Ill (NUTRIC) groups in critically ill patients with body mass index (BMI) <20. Our purpose was to assess whether adequacy of protein/energy intake impacts mortality in patients with BMI <20 in Western/Eastern intensive care units (ICUs) and high/low NUTRIC groups. Methods : Data from the International Nutrition Survey 2013–2014 were dichotomized into Western/Eastern ICU settings; BMI <20 or ≥20; and high (≥5)/low (<5) NUTRIC groups. Association of BMI <20 with 60‐day mortality was compared in unadjusted and adjusted (Western/Eastern, age, medical/surgical admission, high/low NUTRIC group) logistic regression models. The impact of adequacy of protein/energy on 60‐day mortality relationship was tested using general estimating equations in high/low NUTRIC groups, in unadjusted and adjusted models. Results : Western (n = 4274) patients had higher mean BMI (27.9 ± 7.7 versus (vs) 23.4 ± 4.9, P < 0.0001) than Eastern (n = 1375), respectively. BMI <20 was associated with greater mortality (adjusted odds ratio [OR] 1.30, 95% confidence interval [CI] 1.07–1.57), with no interaction between BMI group and Western/Eastern ICU site. Among patients with BMI <20 and high NUTRIC score, 10% greater protein and energy adequacy was associated with 5.7% and 5.5% reduction in 60‐day mortality, respectively. Results were not significantly different between Western and Eastern ICUs. Conclusions : The benefit of greater protein/energy intake in high‐NUTRIC patients was observed regardless of geographic origin or low BMI, suggesting a consistent response to nutrition support in this group. Clinical guidelines and research projects focused on improving care in high‐risk critically ill patients can be applied across geographic boundaries.